RepoMMan user needs analysis - Green, Richard A.; Awre, Christopher L. (The University of Hull)
The RepoMMan Project was established to provide a user interface to a Fedora digital repository which would allow a user to interact with it as an integral part of his or her workflow. In order to understand the requirements of such interactions, the project undertook survey and interview work with three groups of people: those involved in academic research, those involved in teaching and learning (T&L), and those involved in administration. In practice it is accepted that some potential users fit into more than one of these roles. A number of staff at the University of Hull from each of these three groups were interviewed. These interviews typically took 60-80 minutes each and were later transcribed verbatim. Each of the interview transcripts has been reduced to a ‘scenario’ which encapsulates the user needs described. It is not necessarily the case that there is a 1:1 correspondence between an interview and a scenario; some material has been merged. In addition to the interviews, the RepoMMan team conducted an on-line survey of researchers at Hull and elsewhere and assisted the CD-LOR (Community Dimensions of Learning Object Repositories) Project with a similar survey of those involved in T&L. The University of Hull takes a very broad view of the way in which a digital repository might be used. In addition to being a showcase for ‘finished’ digital material, we see potential for the repository to support a user in the production of that material. The investigations thus sought to tease out the essentials of each person’s daily work and working practices, as related to potential digital objects, the type of digital objects that they create, or might create in the future, and thereby to reach an understanding of how a digital repository might help them in the process.